Thermally Conductive Ti3C2T x Fibers with Superior Electrical Conductivity - Yuxiao Zhou; Yali Zhang; Yuheng Pang; Hua Guo; Yongqiang Guo; Mukun Li; Xuetao Shi; Junwei Gu (Nano-Micro Letters)
Highlights The strong covalent crosslinking between trace amounts of borates and the hydroxyl groups of Ti3C2T x significantly reduces interlayer spacing, enhances orientation and compactness, leading to notable improvements in both the mechanical (tensile strength of 188.72 MPa) and electrical properties (7781 S cm−1) of Ti3C2T x fibers. Trace amounts of borates can promote the regularization of interfacial structures, reduce interfacial thermal resistance, and significantly enhance the thermal conductivity (13 W m−1 K−1) of Ti3C2T x fibers, thus increasing their potential for efficient heat transfer applications.